UNDERACHIEVER STUDENT IN LEARNING MATHEMATICS: CAUSES AND SOLUTIONS - Halimatussa'diah Lubis; Jarnawi Afgani Dahlan (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
Underachiever is discrepancy between school achievement and the intelligence level of students, where school achievement is lower than the level of intelligence. This study systematically examines the results of research related to underchiver students. This study aims to identify several factors that are thought to be causes of underachiever student and solutions that can be used to provide appropriate support for students in the process of learning mathematics. The research method used is a systematic literature review with journal criteria, namely the data used is only related to the causative factors and solutions of underachiever students, and the journals used must be indexed by Scopus and Sinta. From the results of the literature study found 169 articles published in national and international journals. Of the 169 articles, 11 articles were selected that met the requirements for the analysis. The results of the analysis show that the causes of underachiever students are internal factors, namely the student's own personality and external factors that come from family and school, then the solutions offered in dealing with underachiever students include the application of fun learning with cognitive and behavioral strategies, psychoeducational interventions in the form of training and learning with approaches are accompanied by a well-prepared strategy for gifted students.